DEVELOPMENT OF THEORETICAL APPROACHES TO PHARMACEUTICAL CARE IMPROVEMENT CONSIDERING THE MODERN REQUIREMENTS OF HEALTH-CARE SYSTEM IN UKRAINE - Zupanets, Igor A; Dobrova, Victoriia Ye; Shilkina, Olena O (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to formulate the theoretical approaches to the improvement of pharmaceutical care considering the modern requirements of the public health system in Ukraine. Methods: The analysis of pharmaceutical care has been performed using policy triangleâ€ model. The pharmaceutical care policy model has been developed by applying the process approach. Results: The model of pharmaceutical care as a structural element of the national health policy has been developed. This model describes mechanisms by which the content, context, and process of the pharmaceutical care policy are influenced by the content, context, and process of the national health policy. Furthermore, we have defined the actors of the pharmaceutical care policy which are groups and organizations of various levels involved in the formation and development of the pharmaceutical care policy. Then, the structure of the pharmaceutical care policy has been elaborated. This policy is integrated into the national health-care system and is adapted to the good pharmacy practice requirements. The center of the policy is a process of pharmaceutical care delivering. The inputs, outcomes, management, and resources that are required for the pharmaceutical care process and provided by the actors have been identified. The data streams within this structure demonstrate implementation of the key elements of the pharmaceutical care process: Patient involvement, patient counseling and education, interprofessional collaboration, documentation of interaction, and follow-up. Furthermore, the mechanism of continual education and increasing of the professional level has been described in this structure. Conclusion: Proposed framework provides a comprehensive view of pharmaceutical care as a structural element of the national health policy considering new trends of the Ukrainian health system. The proposed model of the pharmaceutical care policy allows policy-makers to address all critical-to-quality aspects and stakeholders’ needs.